2015
DOI: 10.1371/journal.pone.0116686
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression in Schizophrenia: Findings from Transcriptional Signatures in Fibroblasts and Blood

Abstract: BackgroundWhole-genome expression studies in the peripheral tissues of patients affected by schizophrenia (SCZ) can provide new insight into the molecular basis of the disorder and innovative biomarkers that may be of great utility in clinical practice. Recent evidence suggests that skin fibroblasts could represent a non-neural peripheral model useful for investigating molecular alterations in psychiatric disorders.MethodsA microarray expression study was conducted comparing skin fibroblast transcriptomic prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 65 publications
2
49
0
Order By: Relevance
“…Immature neurons derived from induced pluripotent stem cells from individuals with schizophrenia have been found to exhibit increased TCF4 RNA expression compared with those derived from healthy controls, 29 suggesting that early developmental disturbances in TCF4 expression are relevant to the disorder. Increased TCF4 RNA expression in fibroblasts and blood from adults with schizophrenia 30 and psychosis 31 has also been reported.…”
Section: J Psychiatry Neurosci 2017;42(3)mentioning
confidence: 85%
“…Immature neurons derived from induced pluripotent stem cells from individuals with schizophrenia have been found to exhibit increased TCF4 RNA expression compared with those derived from healthy controls, 29 suggesting that early developmental disturbances in TCF4 expression are relevant to the disorder. Increased TCF4 RNA expression in fibroblasts and blood from adults with schizophrenia 30 and psychosis 31 has also been reported.…”
Section: J Psychiatry Neurosci 2017;42(3)mentioning
confidence: 85%
“…(2015) [74] A microarray expression study was conducted comparing skin fibroblast transcriptomic profiles from 20 SCZ patients and 20…”
Section: Annexin A5 and Apoptotic Processesmentioning
confidence: 99%
“…In a recent analysis, Cattane et al (2015) performed transcriptome profiling of HDFs from SZ patients and controls using DNA microarrays and RT-qPCR. The study identified 6 differentially expressed genes ( Egr1, Fos, Fosb, Hist2h2be, Jun and Tcf4 ), 5 of which have been previously implicated in the pathophysiology of schizophrenia in postmortem brain, peripheral blood and genetic studies (Forrest et al, 2014; Kurian et al, 2011; Kyosseva, 2004).…”
Section: Understanding Pathophysiological Processes Using Hdfsmentioning
confidence: 99%
“…Prolonged neuroinflammation with glial involvement is a key step in the progression of multiple psychiatric diseases (Leonard, 2007; Müller et al, 2012). Consequently, altered expression of immune and cell-cell communication molecular pathways in HDFs from subjects with MD and SZ (Cattane et al, 2015; Garbett et al, 2015b), as well as BD specific changes in the basal and cytokine-induced tryptophan-kynurenine metabolism (Brown et al, 2014; Johansson et al, 2013a) may reflect disrupted glial inflammatory functions in the brains of diseased individuals.…”
Section: Similarities Between Hdf and Cns Cellsmentioning
confidence: 99%